Penerapan Metode Simple Additive Weighting untuk Pendukung Keputusan Pemilihan Balita Tersehat - Diah Qisqadartunissa; Hendri Irawan; Pipin Farida Ariyani; Reva Ragam Santika (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
This study discusses the application of the Simple Additive Weighting (SAW) method in decision support for the selection of the healthiest toddlers at the Anggrek Bulan Posyandu, Larangan Village, North Larangan District, Tangerang City, Banten Province. In the stage of human growth and development, one of the important processes is during the growth period of toddlers. The growth of toddlers is an important point of success in the quality of subsequent human development. Constraints encountered in this study were the absence of appropriate decision support methods to assist the process of assessing the selection of children under five, so there was no information to determine the nutritional status of children under five and to know the intake of nutritious foods in the growth and development of toddlers, and the selection of the healthiest toddlers was less fast and less effective. The criteria used in the selection of the healthiest toddlers are determined to be 4 (four) namely Height, Weight, Upper Arm Circumference, and Head Circumference. Each criterion has a weight determined by the Chair of the Orchid Month Posyandu and the results of the matrix calculation between alternatives with criteria using the SAW method will produce toddlers who have the healthiest criteria to become the healthiest toddlers. This study resulted in the priority order of the healthiest toddlers in the application of the SAW method at the Orchid Bulan Posyandu. The application of SAW method is used to facilitate the possibility of inputting cost criteria in the future. The SAW method can display an alternative order of priority in the form of the highest to the lowest ranking, is easy to implement, and uses the concept of weighting. This research will produce a proposal for the right method in data processing to make it easier to help the Posyandu head in making decisions. The results of the application of this method are recommendations for the priority order of the healthiest toddlers that can be used as suggestions or input for the Posyandu Chair as a decision-maker in the selection of the healthiest toddlers.